COMMUNICATION OF PEOPLE WITH MENTAL HEALTH DISORDERS IN MILLENIAL GENERATION - Virginia Ayu Sagita; Khuswatun Hasanah; Medi Trilaksono Dwi Abadi; Gabriella Hot Marsondang Simamora (The Indonesian Journal of Communication Studies, 2020)
Mental health is currently a health that must be considered in addition to physical health. According to Riset Kesehatan Dasar (2018), it shows that depression is the highest mental illness and there are 450,000 people who are people with severe mental disorders (ODGJ) who have an age range of 15-29 years. This study aims to see the communication made by survivor of mental health disorders in creating millennials to their closest people. The theory used in this research is Communication Privacy Management Theory (CPM) and Contructivism Theory. CPM theory explains how a person with a health disorder communicates mental illness by considering their personal information. Meanwhile, constructivism theory supports the CPM theory to explain how sufferers of mental health disorders choose the right diction so as not to cause wrong perceptions. Constructivism theory explains how a person constructs the message to be delivered. The method used in this study is a qualitative method with purposive sampling, which is to determine the information required by the researcher. The results of this study are each information that has rules for conveying privacy information to the closest person. The informants' trust with other people still have their privacy boundaries made based on gender, culture and context. In addition, informants used proper diction to convey their mental illness to the closest people.